Ectopic Calcification as Discernible Manifestation in Neonates with Pseudohypoparathyroidism Type 1a - Masanori Adachi; Koji Muroya; Yumi Asakura; Yoichi Kondoh; Jun Ishihara; Tomonobu Hasegawa (International Journal of Endocrinology)
The diagnosis of pseudohypoparathyroidism type 1a (PHP1a) is challenging, because both the osteodystrophy, such as brachydactyly and round face, and the symptomatic hypocalcemia usually develop beyond infancy. Although ectopic calcification may be an early sign of PHP1a, there are no systematic reviews regarding the time of its appearance. We here report on two PHP1a patients who presented with subcutaneous calcification in neonatal period.